Phenotypic and Genomic Variability of Serial Peri-Lung Transplantation Pseudomonas aeruginosa Isolates From Cystic Fibrosis Patients - Datar, Rucha; Coello Pelegrin, Andreu; Orenga, Sylvain; Chalansonnet, Valérie; Mirande, Caroline; Dombrecht, Jill; Perry, John D.; Perry, Audrey; Goossens, Herman; van Belkum, Alex (Frontiers in Microbiology, 2021)
Cystic fibrosis (CF) represents one of the major genetic and chronic lung diseases affecting Caucasians of European descent. Patients with CF suffer from recurring infections that lead to further damage of the lungs. Pulmonary infection due to Pseudomonas aeruginosa is most prevalent, further increasing CF-related mortality. The present study describes the phenotypic and genotypic variations among 36 P. aeruginosa isolates obtained serially from a non-CF and five CF patients before, during and after lung transplantation (LTx). The classical and genomic investigation of these isolates revealed a common mucoid phenotype and only subtle differences in the genomes. Isolates originating from an individual patient shared ≥98.7% average nucleotide identity. However, when considering isolates from different patients, substantial variations in terms of sequence type (ST), virulence factors and antimicrobial resistance genes were observed. Whole genome multi-locus sequence typing confirmed the presence of unique STs per patient regardless of the time from LTx. It was supported by the monophyletic clustering found in the genome-wide phylogeny. The antibiogram shows that ≥91.6% of the isolates were susceptible to amikacin, colistin and tobramycin. For other antibiotics from the panel, isolates frequently showed resistance. Alternatively, a comparative analysis of the 36 P. aeruginosa isolates with 672 strains isolated from diverse ecologies demonstrated clustering of the CF isolates according to the LTx patients from whom they were isolated. We observed that despite LTx and associated measures, all patients remained persistently colonized with similar isolates. The present study shows how whole genome sequencing along with phenotypic analysis can help us understand the evolution of P. aeruginosa over time especially its antibiotic resistance.